2002
DOI: 10.1182/blood.v99.12.4357
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of cytomegalovirus infection after nonmyeloablative stem cell transplantation: potential role of Campath-1H in delaying immune reconstitution

Abstract: Nonmyeloablative conditioning is increasingly used for transplantation in a wide range of diseases, but little is known about its impact on the incidence of infections and immune reconstitution. We examined the pattern and outcome of cytomegalovirus (CMV) infections monitored by polymerase chain reaction-based assays and treated preemptively in 101 patients following nonmyeloablative conditioning containing in vivo Campath-1H. Fifty-one patients (50%) had a CMV infection at a median of 27 days after transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
273
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 348 publications
(297 citation statements)
references
References 28 publications
18
273
6
Order By: Relevance
“…7,14,15,[28][29][30] In addition, relevant changes of patients' characteristics over time led to higher proportion of high-risk patients for CMV-I and CMV-D in the quantPCR period [data not shown], mostly higher proportions of unrelated and mismatched donors (31% in the quantPCR period vs 11% in the pp65Ag period, Po0.01) and in vivo T-cell depleting (20 vs 8%, respectively, Po0.01). 4,9,14,19,31,32 Several observations in this study support that CMV infection and disease are still a frequent and serious complication, with a significant incidence of CMV-D (11%), similar to that observed earlier in alloHSCT-RIC patients. 3,9,31 Of note, 48% of the cases of CMV-D occurred late post transplant (after day þ 100).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…7,14,15,[28][29][30] In addition, relevant changes of patients' characteristics over time led to higher proportion of high-risk patients for CMV-I and CMV-D in the quantPCR period [data not shown], mostly higher proportions of unrelated and mismatched donors (31% in the quantPCR period vs 11% in the pp65Ag period, Po0.01) and in vivo T-cell depleting (20 vs 8%, respectively, Po0.01). 4,9,14,19,31,32 Several observations in this study support that CMV infection and disease are still a frequent and serious complication, with a significant incidence of CMV-D (11%), similar to that observed earlier in alloHSCT-RIC patients. 3,9,31 Of note, 48% of the cases of CMV-D occurred late post transplant (after day þ 100).…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we report a median onset of CMV-I of 57 days, which seems to be delayed compared with RIC regimens based on in vivo T-cell depletion. 4 We also observed that more than half of the patients (24 of 44, 54%) who developed a CMV-I without disease had a recurrence. This observation, in addition to the high rate of late (after day þ 100) episodes of CMV-I and CMV-D (63 and 48%, respectively) have substantial implications.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Alemtuzumab has been scarcely investigated in bone marrow failure syndromes given the specific risk of opportunistic infection from viruses (especially CMV reactivation) and other intracellular pathogens [1,[5][6][7] that would synergize and increase the risk of bacterial complications due to the concomitant neutropenia, especially in SAA. Another concern could be the fear of marrow toxicity deriving from both CMV reactivation and anti-CMV agents.…”
mentioning
confidence: 99%
“…Patients receiving highly immunosuppressive RIC regimens (particularly those containing fludarabine regimens) may be prone to an increased incidence of viral infections such as CMV and EBV. 9 However, with early detection and treatment, death due to reactivation can be avoided.…”
mentioning
confidence: 99%